Reference Gene Selection for qRT-PCR Normalization Analysis in kenaf (Hibiscus cannabinus L.) under Abiotic Stress and Hormonal Stimuli - Niu, Xiaoping; Chen, Meixia; Huang, Xinyu; Chen, Huihuang; Tao, Aifen; Xu, Jiantang; Qi, Jianmin (Frontiers in Plant Science, 2017)
Kenaf (Hibiscus cannabinus), an environmental friendly and economic fiber crop, has a certain tolerance to abiotic stresses. Identification and validation of reliable reference genes for transcript normalization of stress-responsive genes expression by quantitative real-time PCR (qRT-PCR) is important for exploring the molecular mechanisms of plants response to abiotic stresses. In this study, nine candidate reference genes were cloned, and their expression stabilities were assessed in 132 abiotic stress and hormonal stimuli samples of kenaf using geNorm, NormFinder, and BestKeeper algorithms. Results revealed that HcPP2A (Protein phosphatase 2A) and HcACT7 (Actin 7) were the optimum reference genes across all samples; HcUBC (Ubiquitin-conjugating enzyme like protein) was the worst reference gene for transcript normalization. The reliability of the selected reference genes was further confirmed by evaluating the expression profile of HcWRKY28 gene at different stress durations. This work will benefit future studies on discovery of stress-tolerance genes and stress-signaling pathways in this important fiber crop.